2002
DOI: 10.1152/jn.2002.88.4.2104
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Integration Recorded From Vestibular-Only Cells in Response to Position Transients

Abstract: Angular and translational accelerations excite the semicircular canals and otolith organs, respectively. While canal afferents approximately encode head angular velocity due to the biomechanical integration performed by the canals, otolith signals have been found to approximate head translational acceleration. Because central vestibular pathways require velocity and position signals for their operation, the question has been raised as to how the integration of the otolith signals is accomplished. We recorded r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…The majority of these neurons appear to encode velocity or combinations of acceleration and velocity (Angelaki and Dickman 2000;Dickman and Angelaki 2002;Musallam and Tomlinson 2002;Shaikh et al 2005;Yakusheva et al 2008). Response dynamics have also been shown to vary with the direction of motion (Angelaki and Dickman 2000;Musallam and Tomlinson 2002). Using position-transient stimuli, Musallam and Tomlinson (2002) observed spatially asymmetric temporal integration in a population of VN neurons.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of these neurons appear to encode velocity or combinations of acceleration and velocity (Angelaki and Dickman 2000;Dickman and Angelaki 2002;Musallam and Tomlinson 2002;Shaikh et al 2005;Yakusheva et al 2008). Response dynamics have also been shown to vary with the direction of motion (Angelaki and Dickman 2000;Musallam and Tomlinson 2002). Using position-transient stimuli, Musallam and Tomlinson (2002) observed spatially asymmetric temporal integration in a population of VN neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Response dynamics have also been shown to vary with the direction of motion (Angelaki and Dickman 2000;Musallam and Tomlinson 2002). Using position-transient stimuli, Musallam and Tomlinson (2002) observed spatially asymmetric temporal integration in a population of VN neurons. These neurons showed velocity-like responses to translation in one direction, but acceleration-like responses during motion in the opposite direction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Musallam and Tomlinson (2002) found directional asymmetry in the response of vestibular-only (NEM) neurons to linear acceleration transients. In response to unidirectional transient linear accelerations along the nasooccipital and interaural orientations, these authors found that in one direction the cells responded relative to linear velocity, whereas in the other direction the neurons were acceleration sensitive.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, research has revealed the existence of neurons with receptive fields tuned to stimuli or cues relating to displacement, velocity, acceleration, or a mixture of these attributes. Examples of such neuronal classes can be found in the vestibular system of primates [20], the whisker-trigeminal system in rodents [21], the motor cortex of felines [22], and the crab chordotonal organs [18], to name a few. These studies demonstrate the significance and universality of integrating and differentiating modalities in neuronal information coding, from the cellular to the system level.…”
Section: Discussionmentioning
confidence: 99%